RE-FRAMING URBAN GREEN SPACES PLANNING TOWARDS FLOOD RESILIENCE THROUGH SOCIO-ECOLOGICAL RESILIENCE - Afriyanie, Dian
The asymmetric paradigm shift in planning theory has led to an asymmetric development in spatial planning thoughts and practices. In the last half a century, planning content has remained predominantly positivist construct, while planning processes have shown a gradual shift towards post-structuralist. In the ecological context, attention to turn planning theory into the implication of ecological considerations has taken up through political ecology and environmental ethics. However both contributions seem to be limited compared to the extensive focus on the new trajectory of planning theories from collaborative and post-structuralist which demand human-nature relationship to be considered. Under positivist construct through its linier mindset; ways to deal with the complex, unpredictable, historically and geographically variable characteristics of nature have been replaces with techno-managerial planning, expert management and administration, instead of promoting human-nature relationships. In the context of urban green space planning in Indonesia, this reflects in the practice of urban green spaces provision through standard approach which based on population number served. The standard approach has been applied throughout all location in Indonesia without regard to the uniqueness of urban ecosystem in each geographic areas, and the impact of human activities on its future sustainability. The paradigm shift on urban ecology towards “ecology of cities” and “ecology for cities” has provided an opportunity for contemporary planning theory to adopt recent ecological theories which enable promoting human-nature relationship in the planning practices. Socio-ecological resilience (SER) is among of them. The most significant contribution of SER for planning is its role as a different and useful frame for both problem-setting and problem-solving. SER based on assumptions of non-linier dynamics of a linked socio-ecological systems (SESs) which challenged the assumption on equilibrium, stability and predictability of traditional notion on natural resource management; and provide priority to more adaptive modes of governance and attention to cross-scale interaction. Several recent studies applied SER as an analytical method as an alternative to standard approach in determining priority locations of urban green spaces. They analyzesvi the synergies and trade-offs among demand of ecosystem services to determine the priority locations and shown that the current urban green spaces have not consider community needs. However none of them reveal its causes and discuss the disparity between supply and demand of ecosystem services during their analysis to determine the priority locations, especially to consider equitable distribution and resilient supply of ecosystem services. In addition, few studies link the priority locations with urban resilience and climate-related hazard. This research address the gap and utilize three SER propositions through the critical realism methodology. The research applied and advanced several SES and SER framework to analyze socio-ecological system dynamics in study area. Ecosystem Service Framework was applied to analyze the disparity between supply and demand of ecosystem services in examining the equitable distribution and resilient supply of flood protection. The DPSIR Framework was applied to examine how far the existing policies and programs could leverage co-benefit between the priority location of the urban green space with flood mitigation and adaptation measures in order to achieve urban flood resilience. This research advanced Resilience Planning Characteristics Framework, Critical Institutional Analysis and Development Framework, and meta-inferential to analyze governance and its challenges in the implementation of equitable distribution and resilient supply of urban green space planning toward urban resilience in Indonesia. The research area is Bandung City and the Upper Citarum River Basin. The result shows that current and future urban green spaces in Bandung City have not been strategically placed for equitable distribution and resilient supply of ecosystem services. The current spatial planning and strategic environmental assessment have not adequately address urban flood resilience in the future. Those conditions due to the governance of spatial planning and strategis environmental assessment formulation have not been conducted in adaptive-manner. Both normative and analytic challenges in spatial planning practices have caused the non-adaptive governance. These two challenges have caused limited public participation and in-adequate carrying capacity assessment in spatial planning process, in which lead to prioritize economic interests within spatial planning content, and overlooked the previous spatial plan violation. The research findings provide an ecological landscape-based urban green space planning model to address the challenges of urban green space planning in balancing the needs and sustainability of urban ecosystem services. This study also provides new thesis on the challenges of spatial planning practices within science-based policy framework.